Furan-Conjugated Tripeptides as Potent Antitumor Drugs - Hunain Ali; Almas Jabeen; Rukesh Maharjan; Muhammad Nadeem-ul-Haque; Husena Aamra; Salma Nazir; Serab Khan; Hamza Olleik; Marc Maresca; Farzana Shaheen (Biomolecules, 2020)
Cervical cancer is among the leading causes of death in women. Chemotherapy options available for cervical cancer include highly cytotoxic drugs such as taxol, cisplatin, 5-florouracil, and doxorubicin, which are not specific. In the current study, we have identified a new peptide conjugate (Fur4-2-Nal3-Ala2-Phe1-CONH2) (conjugate 4), from screening of a small library of tripeptide-conjugates of furan, as highly potent anticancer compound against human cervical cancer cells (HeLa cells) (IC50 = 0.15 ± 0.05 µg/mL or 0.28 +/− 0.09 µM). Peptides were constructed on Rink amide resin from C- to N-terminus followed by capping by α-furoic acid moiety. The synthesized peptides were purified by recycling RP-HPLC, and structures of all the peptides were confirmed by using FABMS/ESIMS, 1H- NMR, 13C-NMR, and HR-FABMS. Conjugate 4 was furthermore found to be specifically active against human cervical cancer cells since it did not inhibit the proliferation of other human normal cells (HUVEC (human umbilical vein endothelial cells) and IMR-90 (normal human fibroblasts)), and cancer cells tested (HUVEC, MCF-7, and MDA-MB-231 cells), as well as in mice 3T3 cells (normal fibroblasts). This study revealed a good structure activity relationship of various peptide conjugates. Conjugate 4 in branched forms (4a and 4b) were also synthesized and evaluated against HeLa cells, and results revealed that both were inactive. Atomic force microscopy (AFM) studies and staining with rhodamine 123 and propidium iodide (PI) revealed that conjugate 4 possesses a membranolytic effect and causes the loss of mitochondrial membrane potential.